VD_FINDINFO HC / 2012 / 539 vom 23. August 2012 - VD Tribunal cantonal (2012)
DIVORCE, LIQUIDATION DU RÉGIME MATRIMONIAL, OMAN, DROIT ÉTRANGER | 16 LDIP, 52 LDIP, 54 al. 1 let. a LDIP, 54 al. 1 let. b LDIP, 59 LDIP, 62 al. 3 LDIP